1999
DOI: 10.1159/000028844
|View full text |Cite
|
Sign up to set email alerts
|

An Alternate Technique to Close Neurosurgical Incisions Using Octylcyanoacrylate Tissue Adhesive

Abstract: The present authors have applied the use of tissue adhesive octylcyanoacrylate, recently approved by the FDA, in the closure of routine neurosurgical cases. The authors find this to be an excellent substitute for nylon, staples, vicryl or steristrip final layer closure of the surgical incision. This is especially useful in the pediatric neurosurgical practice where young children can be emotionally traumatized by the experience of suture or staple removal. We recommend octylcyanoacrylate closure as a safe, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…11–14 Our study showed that laparoscopic ports closed with OCT had less margin separation and better overall HWES scores. On the other hand, laparoscopic ports closed with OCT had slightly more contour irregularity compared with ports closed with suture.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…11–14 Our study showed that laparoscopic ports closed with OCT had less margin separation and better overall HWES scores. On the other hand, laparoscopic ports closed with OCT had slightly more contour irregularity compared with ports closed with suture.…”
Section: Discussionmentioning
confidence: 70%
“…Additional studies have also demonstrated the successful use of OCT for closure of pediatric surgical incisions 11,12 and neurosurgical incisions of the scalp, back, and torso 13,14 with lower rates of infection and dehiscence. Our study had similar results and showed that abdominal laparoscopic ports closed with OCT had fewer inflammatory reactions, such as erythema and drainage compared with suture.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 CNA skin adhesive is increasingly being used in other surgical specialties such the trauma and emergency departments, as well as the pediatric, gynecology and general surgery departments. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, their use in neurosurgical wounds, where the thickness of the skin is greater, and where there has been a violation of the underlying structures (muscle, bone and dura mater), is a relatively new procedure. Our results, although limited because of the small number of patients involved in combination with the fact that only supratentorial wounds were considered, seem to demonstrate that the NCA used here is clinically effective and safe for the closure of cranial wounds.…”
Section: Discussionmentioning
confidence: 99%
“…This feature may be of particular benefit to pediatric populations, where removal of sutures quite often requires some type of sedation with a prolonged hospital stay. 16,19 During the 6 months of the study, the authors also used CNA in 4 pediatric cases (2 posterior fossa tumors, 1 ventriculoperitoneal shunt and 1 third ventriculostomy), all with excellent anatomical and cosmetic results. The application of CNA might have some advantages for patients with logistical problems, as it removes the need to return to the hospital for suture/clip removal, thereby decreasing wastage of economic resources for transportation; it could thus be of benefit to those who experience poor mobility and require assistance with transportation.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The use of cyanoacrylate-based glue in humans has been recently approved in the United States by the Food and Drug Administration (FDA). 12 The main use of tissue adhesives is for the treatment of skin cuts and lacerations, treated in emergency departments. They are especially useful in children, saving the discomfort associated with placing sutures and their later removal.…”
Section: Discussionmentioning
confidence: 99%